Soundscapes in the German Baltic Sea Before and During the Covid-19 Pandemic - Basan, Fritjof; Fischer, Jens-Georg; Kühnel, Dennis (Frontiers in Marine Science, 2021)
Anthropogenic underwater noise has been identified as one of the main pressures on the marine environment. Considerable research efforts have been made to quantify acoustic soundscapes on different spatial and temporal scales in order to identify trends and investigate how this may impact the marine environment. Measures to reduce noise input into the seas from anthropogenic sources are under discussion, including the reduction of vessel speed or re-routing of shipping lanes. The decline in maritime transport as a consequence of the Covid-19 pandemic provides an opportunity to examine the associated extent of noise reduction. Here, we present the results of a “Before-After-Control-Impact” study where we analyzed acoustic data sets from two monitoring stations in the German Baltic Sea. Data were collected between 2013 and 2020. As part of an international initiative, coordinated by the International Quiet Ocean Experiment, monthly statistics (20 average sound pressure levels per 1/3 octave bands) were calculated from acoustic data collected during the pre-pandemic period (2013–2019), and were compared with data from the year 2020, during the Covid-19 pandemic. To account for varying natural conditions the measurements were sorted into categories of same prevailing sea state. Through this approach, measurements with equivalent natural noise impact are compared and any resulting differences are likely due to the variability in the anthropogenic noise. A decline in sound pressure of 13% (1.2 dB) for low frequencies (10 Hz–1 kHz) was observed at both stations, which corresponds to the reduced level of shipping activity.